The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/pi.5889
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous poly(ethylene oxide)‐based structures incorporated with multi‐walled carbon nanotube and graphene oxide as all‐solid‐state electrolytes for lithium ion batteries

Abstract: Nanofibrous solid polymer electrolytes were prepared using the electrospinning method. These nanofibres were constructed from poly(ethylene oxide), lithium perchlorate and ethylene carbonate, which were incorporated with multi‐walled carbon nanotube (MWCNT) and graphene oxide (GO). The morphological properties of the as‐prepared electrolytes and the interaction between the components of the composites were characterized using scanning electron microscopy and Fourier transform infrared spectroscopy, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…The results showed that increasing of the MWCNTs filler content in the nanofibers led to the formation of the finer fibers. As discussed in the previous study, electrospinning process is influenced by the addition of MWCNT filler into the polymer solution 29 . First, MWCNT particles increase the solution conductivity and lead to the reduction of the fiber's diameter.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The results showed that increasing of the MWCNTs filler content in the nanofibers led to the formation of the finer fibers. As discussed in the previous study, electrospinning process is influenced by the addition of MWCNT filler into the polymer solution 29 . First, MWCNT particles increase the solution conductivity and lead to the reduction of the fiber's diameter.…”
Section: Resultsmentioning
confidence: 95%
“…The obtained data supports the previous studies concluding that the ionic conductivity could be enhanced by the addition of SiO 2 and MWCNT fillers. However, the as‐spun CNT3Si@CS4 membrane illustrated higher ionic conductivity compared with the electrospun structures incorporated with the SiO 2 and MWCNT nanoparticles 29,32 . The observed difference may be assigned to higher ratio of the EC plasticizer content in the electrospun filler‐filled nanofibers.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Overall, many studies have demonstrated that hydroxide conductivity and other performance characteristics of the AEM membranes require further improvement. 26,33,34 Recently, many researchers have sought to enhance the physicochemical properties of the polymer electrolyte membranes by adding fillers such as ionic liquids and inorganic nanoparticles [35][36][37][38][39] (ZrO 2 , 40 SiO 2 , 39 and CNTs [41][42][43][44] ). Wen et al 45 found that addition of ionic liquids in polymer films did enhance the OH − conductivity and performance in SC.…”
Section: Introductionmentioning
confidence: 99%